2012
DOI: 10.1002/lsm.22019
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging of squamous cell carcinoma tumors using topically delivered anti‐EGFR antibody conjugated gold nanorods

Abstract: We have demonstrated that a topical application of gold nanorods targeted specifically to tumor growth factor receptors results in a significantly higher image contrast compared to nontargeted gold nanorods. These results demonstrate the feasibility of near-infrared NBI to image and demarcate tumor margins during surgical resection using topical administration of targeted GNR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…2,26 In addition, their strong NIR plasmon peak (Figure 1) enables them to scatter, absorb or luminesce when excited in the NIR. 27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared).…”
Section: Discussionmentioning
confidence: 99%
“…2,26 In addition, their strong NIR plasmon peak (Figure 1) enables them to scatter, absorb or luminesce when excited in the NIR. 27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared).…”
Section: Discussionmentioning
confidence: 99%
“…However, gold nanoparticles have widely been used for targeted molecular contrast for various applications (28). Tumors are also often passively labeled with gold nanoparticles via the enhanced permeability and retention effect (29).…”
Section: Photothermal Octmentioning
confidence: 99%
“…have spearheaded this research, 106108 which has also been pursued by the group of Tunnell. 109,110 The use of exogenous contrast agents may push the sensitivity and specificity of multiphoton imaging to a point where it can be relied upon in the clinic; however, the regulatory hurdles to the use of any exogenous image contrast agent are considerable.…”
Section: Applications Of Multiphoton Microscopy In Different Areasmentioning
confidence: 99%